2022
DOI: 10.1017/s1368980022000040
|View full text |Cite
|
Sign up to set email alerts
|

Maternal perception of child weight and concern about child overweight mediates the relationship between child weight and feeding practices

Abstract: Objective: To examine the mediating effects of maternal perception of child weight (weight perception) and concern about overweight (weight concern) on the paths between child weight and maternal feeding practices. Setting: Pudong District, Shanghai, China. Participants: A convenience sample of 1164 mothers who were primary caregivers of preschool children. Results: Sixty percent of the mothers perceived their overweight/obese children as normal weight… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 66 publications
1
21
0
Order By: Relevance
“…Characteristics of the included studies are shown in Table 1 . The studies were published between 2001 and 2022, conducted in the US ( n = 12) [ 21 , 24 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ], Australia ( n = 6) [ 26 , 27 , 75 , 76 , 77 , 78 ], Brazil ( n = 4) [ 28 , 30 , 50 , 79 ], Sweden ( n = 4) [ 22 , 80 , 81 , 82 ], China ( n = 2) [ 83 , 84 ], the Netherlands ( n = 1) [ 85 ], Ethiopia ( n = 1) [ 29 ], the UK ( n = 1) [ 86 ], Mexico ( n = 1) [ 87 ], South Korea ( n = 1) [ 88 ], Portugal ( n = 1) [ 23 ], India ( n = 1) [ 25 ], and France ( n = 1) [ 74 ]. The study designs were a cross-sectional study ( n = 32) and a cohort study ( n = 3) [ 23 , 26 , 85 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Characteristics of the included studies are shown in Table 1 . The studies were published between 2001 and 2022, conducted in the US ( n = 12) [ 21 , 24 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ], Australia ( n = 6) [ 26 , 27 , 75 , 76 , 77 , 78 ], Brazil ( n = 4) [ 28 , 30 , 50 , 79 ], Sweden ( n = 4) [ 22 , 80 , 81 , 82 ], China ( n = 2) [ 83 , 84 ], the Netherlands ( n = 1) [ 85 ], Ethiopia ( n = 1) [ 29 ], the UK ( n = 1) [ 86 ], Mexico ( n = 1) [ 87 ], South Korea ( n = 1) [ 88 ], Portugal ( n = 1) [ 23 ], India ( n = 1) [ 25 ], and France ( n = 1) [ 74 ]. The study designs were a cross-sectional study ( n = 32) and a cohort study ( n = 3) [ 23 , 26 , 85 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thirty studies used the subscale of concern about child weight in CFQ to assess caregivers’ concern about children at risk of being overweight [ 19 ], and two studies [ 29 , 77 ] used the Preschooler Feeding Questionnaire (PFQ) [ 89 ] to assess caregivers’ concern about child underweight. CFQ ( n = 21) and the Chinese Child Feeding Questionnaire (C-CFQ) [ 90 ] ( n = 2) [ 83 , 84 ] was used to assess the domains of non-responsive feeding practices, including restriction, pressure to eat, and use of food as a reward. The Comprehensive Feeding Practices Questionnaire (CFPQ) [ 64 ] was also adopted in ten studies to assess caregivers’ restrictions for weight and health, pressure to eat, use of food as a reward, and emotional feeding.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations